Financial Feasibility Analysis of a Manual Forklift Business as a Goods Moving Transport Equipment with a Hand Winch Drive System - Alya, Adinda; Yola, Melfa; Kusumanto, Ismu; Umam, Muhammad Isnaini Hadiyul; Harpito, Harpito (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
Forklifts are a type of heavy equipment in the transport truck category. This tool functions to lift and move objects with large capacity and weight from one location to another. This study aims to determine the financial feasibility of a manual forklift business as a goods moving transport tool with a hand winch drive system in terms of market and marketing aspects, technical aspects and financial aspects. NPV (Net Present Value) is a method to calculate the difference between the present value of future cash inflows and outflows, considering a certain discount rate. IRR (Internal Rate of Return) is the rate of return generated by an investment that makes the NPV equal to zero. AE (Annual Equivalent) is an annual equivalent value that describes the annual profit generated by an investment. DPP (Discounted Payback Period) is the time required to return the initial investment by considering the time value of money. Based on the market and marketing, the selling price of the product using the full costing method is set at around IDR 4,512,000 units, with forecasting the demand for manual forklifts in the future which is expected to increase. Technically, the marketing location of the product was chosen at Jl. Sri Indah, Kec. Rumbai, using the factor rating method. From the financial aspect, with Bank BRI interest rate of 11% as MARR, the development of manual forklifts is considered feasible because it generates a positive NPV of IDR 997.062.647,36, IRR of 16.73%, AE worth IDR 326.437.316,93, and DPP in about 1 year and 6 months.